A review of the genera Cleigastra Macquart, Gonarcticus Becker, Gonatherus Rondani, Hexamitocera Becker, Nanna Strobl, Orthacheta Becker and Spathephilus Becker (Diptera, Scathophagidae) of Russia - Ozerov, A.l.; Krivosheina, M.g. (Zootaxa, 2015)
Flies of the genera Cleigastra Macquart, 1835, Gonarcticus Becker, 1894, Gonatherus Rondani, 1856, Hexamitocera Becker, 1894, Nanna Strobl, 1894, Orthacheta Becker, 1894 and Spathephilus Becker, 1894 (all Scathophagidae) of the fauna of Russia are reviewed. Key to genera, generic descriptions and keys for determination of species are given, and data on geographical distribution are summarized. One species, Nanna cryophila sp. nov., is described as new to science. One new synonymy is proposed: Nanna kamtschatkense (Hendel, 1930) = Nanna tibiella (Zetterstedt, 1838). Orthacheta cornuta (Loew, 1863) is recorded from Europe for the first time. Gonarcticus arcticus (Becker, 1907) is newly recorded from the Palaearctic Region and Russia. Additionally, Nanna flavipes (Fallén, 1819) is newly recorded from China, and Spathephilus nigriventris (Loew, 1864) is newly recorded from Kazakhstan.